EVALUASI POLA FUNGSI RESPON FREKUENSI PADA RESPON GETARAN BANTALAN GELINDING - R Monhendri; Komang Bagiasna (Mesin, 2009)
Rolling bearing is a mechanical component which is commonly used in industrial machinery to suppress mechanical losses due to friction. Health condition of those machines are monitored by measuring its vibration responses as normally conducted in predictive maintenance (PdM) technology. There are two important steps in PdM, i.e. frequency spectrum analysis for diagnostic purpose and control trip value which is based on the root mean square (RMS) vibration level evaluation of the machine in operation. The vibration response measuring results show, the floor noise level contributs to the increase in RMS vibration level. Floor noise found in the frequency spectrum of the rolling bearings vibration resembles the pattern obtained from the frequency response function (FRF) measurements of the rolling bearing assembly unit. The objective of this study is to evaluate the FRF patterns detected in the vibration response of a new rolling bearing installed in the measuring set up. The vibration response and FRF measurements were performed and the frequency spectrum is measured for various shaft rotating speeds as well as static loads. Floor noise signal obtained from frequency spectrums measurement shows a pattern which resembles the FRF curve of the roller bearing measuring set up. The FRF pattern of the floor noise is caused by rolling friction phenomena which generates random vibration excitation signals on the tested rolling bearing and its supporting structure.